Pedestrian Catchment Area Pada Lingkungan Kampus Politeknik Negeri Pontianak - Ikayanti, Palupi; Zulestari, Andi Z; Hasriyanti, Nunik (Politeknik Negeri Pontianak, 2024)
Abstract: Pedestrian paths in Pontianak City are increasingly showing improvement, especially in the city center area where human movement is increasingly busy with various kinds of activities taking place there. Roads as the basic element that forms an area are one of the easiest urban public spaces to observe to understand the characteristics of an area. Actors who travel on the sidewalk face various obstacles and goals they want to achieve during their journey. Walking here is a means to fulfill the need for face-to-face interaction that exists in urban activities. With the uncontrolled growth of urban areas, the development of public spaces for pedestrians is somewhat burdened. Most cities allow citizens to access basic services and needs in walkable areas. Pontianak itself is still dominated by a high number of vehicle users and this is not accompanied by efforts to increase pedestrian comfort. This research aims to determine the obstacles faced by pedestrians, especially in the Pontianak State Polytechnic (Polnep) campus area by measuring the total area that can be passed by pedestrians and assessing pedestrian paths by assessing roads and highways in pedestrian catchment areas. feet at every intersection. . The research method used is a non-probability sampling method, namely an accidental sampling technique to calculate the pedestrian catchment area on the Polnep campus to determine the total pedestrian catchment area that is still comfortable to walk through. By measuring the distance between two nodes by navigating the street layout, urban morphology can impact the measurement of the ratio of route distance to urban distance. The analytical method used in this research is qualitative and quantitative descriptive analysis. Qualitative descriptive analysis is used to describe the results of observations and interpretation of quantitative data presented in tabular form. Meanwhile, the quantitative descriptive analysis method is used to measure or assess user perceptions of walkability quality based on the walkability aspects studied, namely accessibility, comfort, safety and aesthetics. The results and findings of the analysis at the Pontianak State Polytechnic Campus show that Accessibility (A), Security (SAF), Comfort (COM), and Aesthetics or Beauty (AES) have a partial and significant effect on Walkability. The conclusion can be proven through the results of the T test (partial) where the calculated T value for each variable is greater than the T table and the significance value for each variable is <0.05.